(3GdQbGHI Ydi CYeGd GdSdWI GdJfajPjI aj GdeedcI GdYQHjI GdSYhOjI (B: s (3OQGSI hUajI JMdjdI ebGQfI (B/ s - (3YUGe Hf SYO Hf YHO GdYRjR Hf SYjO s; (3LGHQ LGO fUGQ (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2010)
(3GdfXGe ai GdeedcI GdYQHjI GdSYhOjI fXGe edci dg bhGYO hVhGHW eMOOI JhVM YdGbI GdSdWI GdJfajPjI HGdSdWI GdJTQjYjI hGdbVGFjI hcjajI JchjfgG heeGQSJgG egeGJgG hMOhO GdQbGHI Ydi CYeGdgG (B. (3hehVhY gPG GdHMK (B" (3GdQbGHI Ydi CYeGd GdSdWI GdJfajPjI ai GdeedcI GdYQHjI GdSYhOjI(B" (3heOdhd Jdc GdQbGHI hGdCLgRI GdefhW HgG Pdc hCSGdjH Yed hJbhje gPg GdQbGHI hcjajI Jchjf GdSdWI GdJfajPjI hYdGbGJ GdJYGhf hGdJhGRf HjfgG hHjf SdWGJ GdOhdI GdCNQis
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B2010.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B595 - 627.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdOSJhQjs; (3GdSdWI GdJfajPjIs; (3CYeGd GdSdWIs; (3QbGHI GdSdWI s; (3eLdS GdhRQGAs; (3GdSdWI GdbVGFjIs; (3Mbhb GdEfSGfs; (3GdSdWI GdJTQjYjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs